Análise da resposta Th17 em líquen plano oral - Monteiro, Barbara Vanessa de Brito (2012)
Th17 cells have been strongly associated with the pathogenesis of several autoimmune and inflammatory diseases. IL-17 and IL-23 are important cytokines associated with this lineage. The aim of this study was to analyze, through immunohistochemical methods, the immunoexpression of IL-17 and IL-23 in the inflammatory infiltrate of oral lichen planus (OLP) lesion compared to that of inflammatory fibrous hyperplasia (IFH) and between clinical forms reticular and erosive of OLP. The sample included 41 cases of OLP, of which 23 were reticular and 18 erosive and 10 cases of IFH. The results were subjected to nonparametric statistical tests with a 5% significance level. In OLP lesions histomorphological analysis, the most common findings were: hyperparakeratinization, specimens with atrophic epithelium in erosive clinical form (p = 0.011), epithelial projections in most of reticular type of lesions, in addition Civatte bodies were identified in most samples of both clinical forms. For immunohistochemistry analysis, five fields with strong immunoreactivity for IL-17 and IL-23 were photomicrographed at 400x magnification, images were transferred to a computer where with ImageJ software®, lymphocytes that exhibited cytoplasmic immunostaining for these cytokines were counted. A mean was established after for each case. There was no statistically significant difference in the number of imunopositive lymphocytes for IL-17 and IL-23 among the group of OLP and IFH group, however a larger amount of lymphocytes imunopositive for IL-17 was found in the LPO group (p = 0.079) and significantly higher amounts of those lymphocytes were found in the erosive OLP when compared to the group of reticular OLP and IFH (p = 0.019). Furthermore, a marker epithelial immunopositivity for IL-17 was observed in OLP group. Although the results of this study do not permit the forceful assertion about the participation of Th17 lineage in OLP lesions, the findings of immunopositive lymphocytes counting for IL-17 and IL-23, which are potent proinflammatory cytokines, together with the the marked epithelial immunopositivity found for IL-17 in this study, suggest a possible role of this lineage in the pathogenesis of this disorder